The representation of entrepreneurship in people with disabilities: A discourse analysis - Pilar Ortiz-García; Ángel José Olaz Capitán (Administrative Sciences, 2025)
The aim of this paper is to identify the main moderating aspects of entrepreneurship in people with disabilities in Spain in relation to the main explanatory theories on the subject via a discourse analysis of a group of entrepreneurs and qualified witnesses. Several key elements were identified in this analysis: physical, accessible, and familial. Attention to these aspects will contribute to the empowerment of a group at a clear disadvantage compared to others without disabilities in the entrepreneurial processes. This research proposes the acquisition, stimulation, and development of a set of knowledge, skills, and abilities (competencies) together with a greater commitment on the part of the Public Administration and awareness of society in order to reverse the current starting conditions of this group.
Keywords: 350; competencies; disability; empowerment; entrepreneurship